Synthesis and characterization of N-octanoyl glycol chitosan as a novel temperature and pH-sensitive injectable hydrogel for biomedical applications - Hoang-Minh Pham; Chanyang Joo; Mst Jannatul Ferdous; Israr Ali; Sun-Woong Kang; Kang Moo Huh (Materials & Design)
Multi-responsive hydrogel formulations have received significant attention in biomedical applications as promising injectable depots and platforms for tissue regeneration. In this study, a new pH- and temperature-sensitive polymer, octanoyl glycol chitosan (OGC), synthesized by controlled N-octanoylation of glycol chitosan and evaluated as a reversible hydrogel system capable of undergoing sol–gel transition in response to changes in pH and temperature. The OGC hydrogels, with varying degrees of octanoylation (DO), were characterized by 1H NMR and ATR-FTIR analyses, and their physicochemical properties were evaluated in terms of injectability, thermo- and pH-sensitivity, biodegradability, self-healing, cytotoxicity, 3D cell culture support, and in vivo biocompatibility. The OGC exhibited controlled thermosensitive sol–gel transition behavior, with transition temperature ranging from 23 °C to 58 °C, which could be tuned by adjusting the DO and polymer concentration. The effect of pH on gelation was also observed within the pH range of 5 to 7.4. OGC demonstrated excellent injectability and self-healing properties. In scaffold-free 3D cell culture systems, the OGC supported spheroid formation and maintained stability for up to 7 days. In vivo studies in ICR mice revealed no significant inflammatory response upon implantation. These results suggest that the OGC could be a promising injectable biomaterial for various biomedical applications.